2021
DOI: 10.1152/japplphysiol.01066.2020
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced splenic volume and contraction in elite endurance athletes

Abstract: Splenic contraction, which leads to ejection of stored erythrocytes, is greater in athletes involved in regular freediving or high-altitude activities. As this response facilitates oxygen carrying capacity, similar characteristics may be expected of elite endurance athletes. Therefore, our aims were to compare resting and apnea-induced splenic volume in endurance athletes and untrained individuals, and to assess the athletes' exercise-induced splenic volume. Twelve elite biathletes (7 women) and 12 controls (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…However, the role of the spleen in O 2 transport during aerobic exercise has not been carefully studied. Moreover, direct evidence that splenic contraction also augments aerobic performance during exercise in humans is lacking, as there is still an on-going debate in the literature regarding the role of the spleen in O 2 transport under different scenarios (Gatterer and Burtscher 2021 ; Schagatay and Holmström 2021 ; Holmström et al 2021b ). Therefore, the correlation between the spleen volume changes, circulating RBC release and uptake parameters was explored here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of the spleen in O 2 transport during aerobic exercise has not been carefully studied. Moreover, direct evidence that splenic contraction also augments aerobic performance during exercise in humans is lacking, as there is still an on-going debate in the literature regarding the role of the spleen in O 2 transport under different scenarios (Gatterer and Burtscher 2021 ; Schagatay and Holmström 2021 ; Holmström et al 2021b ). Therefore, the correlation between the spleen volume changes, circulating RBC release and uptake parameters was explored here.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we reasoned that the reduction in splenic volume during supine cycling would be clearly observed, while the on-going debate in the literature regarding the role of the spleen in oxygen transport during aerobic exercise warrants further investigation. Recent work by Holmström and co-authors ( 2021b ) suggested that apnea-induced splenic contraction (reduction in splenic volume by ~ 46) leads to a transient increase in Hb concentration (by 4.5%), and thereby arguments O 2 uptake in endurance trained athletes, but not in sedentary controls. This, however, contradicts recently published short report, in which we found no correlation between max.…”
Section: Introductionmentioning
confidence: 99%
“…The spleen varies in size between individuals, but it is typically ~ 10 × 6 × 3 cm 3 , weighs ~ 120 g, and is highly vascularized, storing 20–30% of total blood volume [ 21 ]. Larger-than normal spleen sizes have been reported in “Sea Nomads” (or Bajau people) who engage in breath-hold diving and in elite endurance athletes [ 25 , 26 ]. Although splenic contraction is a part of the human diving response, it is thought that those who engage in breath-hold diving have physiologically and genetically adapted to the hypoxic environment, which has led to the development of a larger-than normal sized spleen.…”
Section: Biology Of the Spleenmentioning
confidence: 99%
“…On the other hand, ultrasonography is a useful non-invasive, portable method, which is applicable in both laboratory settings and during fieldwork contexts. Ultrasonic imaging is particularly suited to experiments involving various stressors, such as maximal exercise 3 , 16 , voluntary apnea 8 , 17 , normobaric hypoxia 18 or hypobaric hypoxia 19 , which often includes a time-constrained protocol where windows for collection of splenic measurements are short. The length of the spleen display a strong correlation with splenic volumes from measures of cadavers 20 and with CT scan measurements 14 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, other formulas exist, one, in particular, was designed to account for individual differences in splenic diameters, which could plausibly result in varying splenic volumes. This particular formula has been broadly used in physiological laboratory research, involving apneic diving 8 , 25 , 26 , normobaric hypoxia exposure 18 , 27 29 and during maximal exercise 16 . Additionally, it has been used during field-based contexts involving hypobaric hypoxia and exercise 17 , 19 , 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%